Language And Gender Dynamics: How Speech Shapes Social Roles In Men’s Rights And Feminism - Antonetta, Vinlie; Jasmine, Shoofy; Arianto, Shakira Dwi Azura; Rangkuti , Rahmadsyah (Innovative: Journal Of Social Science Research, 2024)
This journal examines the dynamics of language as it relates to gender roles in the context of the Men’s Rights and Feminism movements, using data drawn from the YouTube video “Men’s Rights vs Feminism: Is Toxic Masculinity Real? | Middle Ground.” By analyzing the interaction and discourse between male and female participants, we explore how speech patterns reflect and reinforce gendered expectations, emotional expression, and social hierarchies. We employ a pragmatic sociolinguistic framework to study how the participants’ conversations about toxic masculinity, emotional repression, and the definition of strength provide insights into the shaping of social roles within these two ideological perspectives.